An optimized MNK1b aptamer, apMNKQ2, and its potential use as a therapeutic agent in breast cancer - C. Pinto-Díez; R. Ferreras-Martín; R. Carrión-Marchante; J.I. Klett-Mingo; M. García-Hernández; M.I. Pérez-Morgado; S. Sacristán; M. Barragán; M. Seijo-Vila; I. Tundidor; S. Blasco-Benito; E. Pérez-Gómez; et al. (Elsevier, 2022)
Breast cancer is the most commonly diagnosed and leading cause of cancer death among women worldwide. Mitogen-activated protein kinase-interacting kinases (MNKs) promote the expression of several oncogenic proteins and are overexpressed in several types of cancer. In human cells, there are four isoforms of MNKs. The truncated isoform MNK1b, first described in our laboratory, has a higher basal activity and is constitutively active. Aptamers are emerging in recent years as potential therapeutic agents that show significant advantages over drugs of other nature. We have previously obtained and characterized a highly specific aptamer against MNK1b, named apMNK2F, with a dissociation constant in the nanomolar range, which produces significant inhibition of proliferation, migration, and colony formation in breast cancer cells. Furthermore, its sequence analysis predicted two G-quadruplex structures. In this work, we show the optimization process of the aptamer to reduce its size, improving its stability. The obtained aptamer, named apMNKQ2, is able to inhibit proliferation, colony formation, migration, and invasion in breast cancer cells. In murine models of breast cancer, apMNKQ2 has demonstrated its efficacy in reducing tumor volume and the number of metastases. In conclusion, apMNKQ2 could be used as an anti-tumor drug in the future.